Analysis of Revealed Comparative Advantage and Constant Market Share in Indonesian Horticultural Products - Rakhmawati, febri; Fesalica, Cizelia (Inovasi Analisis Data, 2024)
This study undertakes a comparative analysis, focusing on Revealed Comparative Advantage (RCA) and Continuous Market Share (CMS) in the Indonesian flower seeds sector. Primary data sourced from the Bureau of Statistics (BPS) and Trademap, alongside secondary data from official websites of Indonesia's Ministry of Commerce and Ministry of Agriculture, are utilized. The study examines five fruit varieties (pineapple, banana, mango, orange, and mangosteen) and their trade relations with four key partner countries (Netherlands, Singapore, Malaysia, and the United States). The analysis reveals pineapple as a promising commodity for Indonesia to compete globally. Recognizing this potential, concerted efforts are being made by the Indonesian government, particularly the Ministry of Commerce, Ministry of Agriculture, and Ministry of Economic Cooperation, to foster a coordinated approach. The aim is to tap into international markets, notably the United States, through strategic policies supporting the development of Indonesian horticultural businesses, enhancing their global competitiveness.